Design and rapid levelling control strategy of omnidirectional levelling system for tractor seat in hilly and mountainous terrain - Li, Chen; Zhang, Junjiang; Ge, Shuaishuai; Liu, Mengnan; Xu, Liyou; Yan, Xianghai (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
To address the problem of reduced comfort caused by vehicle tilt for tractor drivers in hilly terrain, a novel seat posture omnidirectional levelling system is designed, and an omnidirectional rapid levelling control strategy (QBP-PID) is proposed, which fuses Q-learning, back propagation (BP) neural network, and proportional-integral-derivative (PID) control. Firstly, an omnidirectional levelling system for seat posture is designed based on kinematic principles. On this basis, a model for the omnidirectional levelling system is established using valve-controlled hydraulic cylinder principles. Subsequently, addressing the challenge of difficult parameter tuning for the levelling system’s PID control, a multi-level parameter update strategy employing QBP-PID is proposed for rapid omnidirectional levelling control. Simulation results show that under QBP-PID control, the 15◦ lateral levelling time is 2.98 s with an overshoot of 0.32◦; meanwhile, longitudinal levelling time at 20◦ is 3.41 s with an overshoot of 0.95◦. Compared to BP-PID and PID, lateral levelling time is reduced by 18.13% and 27.66%, respectively, while longitudinal levelling time decreases by 17.63% and 31.6%, respectively. The superiority of the QBP-PID omnidirectional rapid levelling control strategy is thus demonstrated.